Increasing the Learning Motivation of Three-Dimensional Material for 5th Grade in Public Elementary School 2 Palaan Through SALAM Media "Snake & Ladder Math" - Halimatus Sa`diyah; Atiris Syari’ah; Indah Nur Hikmatus Shoumi; Ainur Rohmah; Imam Buchori (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Sometimes, it is easy for students to feel bored during the learning process. The saturation experienced by students can be caused by the large amount of material that must be mastered, one of which is Three-Dimensional material. In elementary school, mathematics is generally a less desirable subject. Therefore, elementary school teachers need to package it using learning media that are in accordance with students' character. This community services seeks to trace the effective learning media applied in 5th grade of SDN 2 Palaan through a descriptive approach and inductively analysis. The result is that the SALAM learning media "Snake & Ladder Math" is an appropriate learning media for Three-Dimensional material.